Postpartum metabolic syndrome after gestational hypertension and preeclampsia, a prospective cohort study - OSOTI, Alfred O. (Pregnancy Hypertens, 2019)
OBJECTIVE: We evaluated the 6-month postpartum risk of metabolic syndrome (MetS), a marker of future cardiovascular disease (CVD) risk, comparing women whose most recent pregnancies were complicated with gestational hypertension (GH) or preeclampsia (PE) versus those who had normotensive pregnancies. STUDY DESIGN: This was a prospective cohort study in which women with GH or PE and normotensive women were actively enrolled during the first 12 weeks after delivery in Nairobi, Kenya. Participants were interviewed, blood pressures and anthropometric measurements including waist circumference obtained at enrollment and 6 months postpartum. Fasting lipid profile and plasma glucose were measured at 6 months postpartum. A generalized linear regression model with Poisson distribution was used to estimate crude relative risk (RR) of 6-month postpartum MetS and adjusted RR (ARR) after adjusting for apriori potential confounders. RESULTS: Among 194 postpartum, 63 (32%) had experienced GH or PE. Prevalence of MetS at 6 months postpartum was higher among women whose pregnancies were complicated with GH or PE (34.9%) compared to those who were normotensive (11.5%). GH and PE was associated with a 3-fold or greater risk of MetS (ARR) 3.01; 95% Confidence interval [CI] 1.58, 5.71; p<0.001) overall and three of the five components, namely hypertension (ARR 3.35 [2.04, 5.51], p<0.001), hypertriglyceridemia (ARR 3.25 [1.16–9.10], p=0.01), and fasting hyperglycemia (ARR 6.20 [1.07–35.76], p=0.03), compared to having normal blood pressures during pregnancy. CONCLUSION: At 6 months postpartum, GH and PE were associated with three-fold or higher risk of MetS and especially hypertension, fasting hypertriglyceridemia, and fasting hyperglycemia.